2016
DOI: 10.1017/s1751731116000744
|View full text |Cite
|
Sign up to set email alerts
|

A decision-tree model to detect post-calving diseases based on rumination, activity, milk yield, BW and voluntary visits to the milking robot

Abstract: Early detection of post-calving health problems is critical for dairy operations. Separating sick cows from the herd is important, especially in robotic-milking dairy farms, where searching for a sick cow can disturb the other cows' routine. The objectives of this study were to develop and apply a behaviour-and performance-based health-detection model to post-calving cows in a roboticmilking dairy farm, with the aim of detecting sick cows based on available commercial sensors. The study was conducted in an Isr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
2
26
0
2
Order By: Relevance
“…Similarly, temperature around a sick cattle’s gluteal region differs significantly from those of other parts when studied using thermal infrared scanning [ 57 ]. As reported by Steensels et al [ 58 , 59 ], temperature management in poultry, as well as early mastitis identification are some other areas where thermal scanning was reported to be useful.…”
Section: Related Literaturementioning
confidence: 98%
“…Similarly, temperature around a sick cattle’s gluteal region differs significantly from those of other parts when studied using thermal infrared scanning [ 57 ]. As reported by Steensels et al [ 58 , 59 ], temperature management in poultry, as well as early mastitis identification are some other areas where thermal scanning was reported to be useful.…”
Section: Related Literaturementioning
confidence: 98%
“…The independent variables can be either categorical or continuous (Ma, 2018). Steensels et al (2016) developed a CART model to detect postcalving lameness and metritis, and reported acceptable sensitivity and specificity at 69 and 87%, respectively. CARTs have also been used to predict difficult calvings (Zaborski et al, 2016;Fenlon et al, 2017).…”
Section: Classification and Regression Treesmentioning
confidence: 99%
“…1. L'élevage de précision pour mieux prédire la santé et le bien-être des animaux grâce aux données de comportement Plusieurs systèmes d'EdP (tableau 1) sont proposés afin de détecter précocement les troubles de santé, ceux-ci ayant des répercussions économiques importantes (Steensels et al, 2016 ;Steensels et al, 2017).…”
Section: Introductionunclassified